Fluorinated metal-organic frameworks: advantageous for higher H-2 and CO2 adsorption or not? - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemistry-A European Journal, 2012)
The synthesis, structure, and gas adsorption properties of three new metalorganic frameworks (MOFs) designed from isonicotinic acid (INA) and its fluorinated analogue 3-fluoroisonicotinic acid (FINA) along with CoII as the metal center have been reported. Co-INA-1 ([Co3(INA)4(O)(C2H5OH)3][NO3].C2H5OH.3?H2O; INA=isonicotinic acid) and Co-INA-2 ([Co(INA)2].DMF) are structural isomers as are Co-FINA-1 ([Co3(FINA)4(O)(C2H5OH)2].H2O; FINA=3-fluoroisonicotinic acid) and Co-FINA-2 ([Co(FINA)2].H2O), but the most important thing to note here is that Co-INA-1 and Co-FINA-1 are isostructural as are Co-INA-2 and Co-FINA-2. The effect of partial introduction of fluorine atoms into the framework on the gas uptake properties of MOFs having similar structures has been analyzed experimentally and computationally in isostructural MOFs.
Keywords: cobalt; fluorine; Hydrogen storage; metal-organic frameworks; microporous materials; X-ray diffraction

Four 3D Cd(II)-based metal organic hybrids with different N,N `-donor spacers: syntheses, characterizations, and selective gas adsorption properties - Bhattacharya, Biswajit; Dey, Rajdip; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (Crystal Growth & Design, 2013)
{Four new metal organic frameworks with bivalent cadmium, disodium succinate (Na(2)suc), and four different N,N'-donor ligands, i.e., {[Cd(L1)(suc)]center dot(H2O)(3)}(n) (1), {[Cd(L2)(suc)]center dot(H2O)(2)\

Flexible dicarboxylate based pillar-layer metal organic frameworks: differences in structure and porosity by tuning the pyridyl based N, N ` linkers - Dey, Rajdip; Bhattacharya, Biswajit; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (CrystEngComm, 2014)
{Dicarboxylate supported metal organic hybrids of Co(II), Zn(II) and Cd(II) have been synthesized using two different pyridyl based N, N' linkers having Schiff base functionalized site. The use of flexible dicarboxylate glutarate in designing such frameworks has created a marked diversity in topology. The different N, N' donor linkers also played an active part in the channel modification in the synthesized MOFs. The structural and topological diversity has been analyzed from the single crystal X-ray structure. Five compounds, {[Co(azpy)(glut)]center dot(CH3OH)}(n) (1), {[Co(meazpy)(glut)(H2O)(2)]center dot (H2O)(3)

Functionalization and isoreticulation in a series of metal-organic frameworks derived from pyridinecarboxylates - Pachfule, Pradip; Garai, Bikash; Banerjee, Rahul (Inorganic Chemistry, 2016)
The partially fluorinated metal-organic frameworks (F-MOFs) have been constructed from 3-fltoro-4-pyridinecarboxylic acid and trans-3-fluoro-4-pyridineacrylic acid linkers using Mn2+, Co2+, and, Cd2+ metals via the solvothetrnal method, which show isostructural isomerism with their nonfluorinated counterparts synthesized using 4-pyridinecarboxylic acid and trans-4-pyridineacrylic acid, respectively. The simultaneous effect of partial fluorination and isoreticulation on structure and H-2 adsorption has been studied systematically in isostructural nonfluorinated and partially fluorinated MOFs, which shows that the increment in the hydrogen uptake properties in F-MOFs is not a universal phenomenon but is rather system-specific and changes from one system to another.